Educational activities for safeguarding of the cultural heritage in the chitalishte – problems and perspectives (Research Announcements "Heritage BG", 2025)
In Bulgarian among the main institutions directly involved in the safeguarding of cultural heritage – tangible and intangible, are the chitalishta. Many of them maintain museum and archive collections, have an experience in safeguarding and socializating the typical for the village traditions. Various directly educational initiatives such as discourses and workshops are organized, temporary and permanent folklore groups where training takes place in the intangible cultural heritage and where older people pass on the inherited knowledge and skills and young people and children are encouraged to safeguard them. The research will present the main problems in the educational activities developed by the Chitalishta in the field of cultural heritage and will offer possible solutions for overcoming them in the context of the in the Chitalishta legislation and the implementation cultural policies. References:Konvencia 2003: Convention for the Safeguarding of the Intangible Cultural Heritage: https://ich.unesco.org/doc/src/00009-BG-PDF.pdfNaredba 2009: Naredba 6 za formirane, upravlenie I identifikatcia na muzejnite fondove: https://www.lex.bg/en/laws/ldoc/2135657162Nenova 2019: Nenova, Stela. Obshtnosti i chitalishtna institutsia v sahranyavaneto na nematerialnoto kulturno nasledstvo – normativni dokumenti i praktiki. – Bulgarski folklore, № 1, 32–49.Nenova 2016: Bulgrian chitalishta and safeguarding of folklore. PhD Dissertation, IEFEM. Sofia.Santova 2014: Santova, Mila. To Capture the Elusive. Intangible Cultural Heritage. Sofia AP ‘Prof. Marin Drinov’.Stanoeva 2021: Stanoeva, Iva. Chitalishta and Intangible Cultural Heritage – Opening New Fields. – In: Intangible Cultural Heritage, Current problems. M. Santova, V. Ganeva-Raycheva i dr. (eds.) 153– 165, Sofia AP ‘Prof. Marin Drinov’.Zakon 1996: Zakon za narodnite chitalishta: https://www.lex.bg/laws/ldoc/2133897729Zakon 2009: Zakon za natcionalnia arhiven fond: https://www.lex.bg/laws/ldoc/2135557636
Keywords: chitalishta; education; legislation; cultural heritage; safeguarding